When Tech Meets Touch: Multistakeholder Perspectives and Implementation Strategies for eHealth in Chronic Kidney Disease: A Systematic Review Using Computational Linguistics. - Zheng, Xutong; Xie, Liuxuan; Liu, Yingshuo; Yu, Qiuying; Zhang, Han; Zhang, Xiao; Wang, Aiping; Matthew Vandermeulen (Journal of Nursing Management, 2026)
Background: Chronic kidney disease heavily burdens patients and health systems. Digital health interventions offer significant potential but face implementation challenges driven by stakeholders' emotional and practical experiences. This review synthesizes these affective dimensions to inform clinical practice. Methods: A qualitative systematic review was conducted across six databases for studies published through April 2025. Methodological quality was rigorously appraised. We integrated Python‐based computational sentiment analysis to quantify stakeholder emotional polarity (positive, negative, neutral) with thematic analysis. Identified barriers were mapped to established implementation frameworks to select expert‐validated implementation strategies. Results: Twenty‐three qualitative studies were included, revealing five domains: accessibility, communication, workflow, empowerment, and clinical effectiveness. Patients praised digital empowerment but highlighted socioeconomic access barriers. Nurses valued workflow efficiencies but reported role ambiguity. Clinicians expressed deep skepticism toward remote clinical effectiveness due to diagnostic limitations. To resolve these tensions, prioritized implementation strategies include identifying clinical champions, promoting intervention adaptability, and systematically assessing organizational readiness before deployment. Conclusion: Stakeholder emotions critically dictate digital health adoption. For clinical practice, these findings emphasize moving beyond generic deployments. Healthcare systems must address clinician diagnostic concerns via hybrid care models, resolve nurse workflow ambiguities through targeted training, and provide low‐cost devices to bridge patient equity gaps. Tailoring solutions to these psychosocial needs is essential for successful integration into routine kidney care.